Rizal without the overcoat - Ocampo, Ambeth R. 1961- (Mandaluyong City, Philippines Anvil Publishing, Inc., 2022)
"This book is a collection of essays from Ambeth R. Ocampo’s newspaper column “Looking Back” that began in the Philippine Daily Globe and later moved to the Philippine Daily Inquirer. He presents a readable and painless introduction to Jose Rizal and offers fascinating insights, lively anecdotes, academic intrigue, and little-known facts about the hero as human. Investigating Rizal’s own writings - his diaries, letters, and other papers – Ocampo attempts to strip the countless myths and rumors that surround the national hero."
MANY RIZALS: Rizal did not write "Sa Aking Mga Kabata" -- Why Rizal is the national hero? -- Was Rizal an American-sponsored hero? -- Deflating the historical ego -- Rizal's trip to America -- Rizal's anti-Americanism -- Recto's Rizal Bill -- FACTS AND POSSIBILITIES: Rizal: Father of Hitler? Jack the Ripper? -- Is Rizal really still alive? -- Was Rizal psychic? -- The psychic in Rizal -- The writ that could have changed history -- Rizal's new Calamba in Sabah -- FAMILY AND OTHERS: Discovery in Binan -- The other Rizal -- Look for priests in your closet -- Blumentritt's role in the propaganda war -- The Ventura shipment -- Recuerdos de patay -- Ho Chi Minh and Rizal -- EVERYDAY RIZAL: Rizal ate tuyo for breakfast -- In Rizal's service -- Rizal: stingy or thrifty? -- What Dr. Rizal's clinic was like? -- Of smoker's street and betel nuts -- What did Rizal read? -- The bookworm in Rizal -- Luna, in a letter to Rizal -- The great Dapitan stock market -- Rizal as role model for students -- THE LEGENDARY TALENT: Rizal and Orwell -- Rizal on Domingo de Ramos -- The Noli could have been a cookbook -- Lusty passages from Rizal's Noli me Tangere -- The house on Anloague Street -- The Noli me tangere: a century after -- Comparing 'Noli' translations by computer -- The matter of reading Rizal's novels -- One hundred years of the Fili -- Rizal's third novel -- Rizal's unsigned and untitled poem -- Overnight poetry -- Translations of 'Ultimo Adios' -- THE NEVER-ENDING STORY: Living with Rizal: an interview with Rizal biographer Austin Coates -- "Rizal was the victim of a struggle between Spain and Spain": an interview with Manuel Sarkisyanz -- OTHER VIEWS: Rizal's dream -- Rizal's last letters -- Leave Rizal's pieces in peace -- A sensational theft -- Rizal and Mariang Makiling -- Rizal's vital statistics -- What penmanship of our heroes reveals -- The Artist in Rizal -- Was Rizal the prime mover of the revolution? -- Recto on Rizal -- AT HOME AND ABROAD: Rizal, father of Philippine Komiks -- Rizal's prescription for kulam -- Rizal's assets -- Expensive mistakes -- Where/How did you learn English? -- Rizal impersonating a Japanese -- Fleecing the innocents in Rizal's time -- Rizal's letters in English -- The Pasig River starts to live again -- Rizal in the British Library -- The interior designer in Rizal -- Handwriting on the wall: Rizal, the teacher, and his students -- Rizal in far-off Dapitan -- Rizal's poetry in Dapitan -- Seeing beneath Rizal's greatness -- Rizal and children -- Rizal, the farmer and businessman -- Rizal's wide-ranging medical practice -- OUR RIZALS (the 1996 Inquirer Rizal series): Was Rizal a fence-sitter? -- Did Rizal retract from Masonry? -- Was Rizal prophetic or a conscious hero? -- Did the Katipunan frame Rizal? -- A centennial Rizal did not want -- 'Oh, what a beautiful morning!' -- More dangerous dead than alive -- Rizal monument up close and personal.
"Revised and expanded."--Cover.
Includes bibliographical references (pages [241]-242)
Winner [of] National Book Awards: Essay [by] NBDB/MCC.
Keywords: Rizal, Jose -- 1861-1896.